Borris Gorrelik, An Entirely Different World: Russian Visitors to the Cape, 1797– 1870 (Historia, 2021)
This new addition to the Van Riebeeck Society’s collection is one that tells the story of the early Cape colonial narrative in a particularly unique fashion – through the eyes of a relatively under-represented group of European travellers. Although Russianvisitors to the Cape do not take centre stage in the historic narrative, many made their way around the treacherous Cape Point. Until the opening of the Suez Canal in 1869, Russian ships had to travel halfway around the globe to reach Russia’s eastern domains. For this voyage one of two alternative routes could be followed, around Cape Horn or around the Cape of Good Hope. Many made the journey around the southern tip of Africa and during these travels stopped at the Cape of Good Hope to take in new supplies and make repairs. It was during these stopovers that some of the most interesting Russian accounts of the Cape were jotted down and these unique insights were preserved for posterity. Now these accounts have finally been translated and are available both to lay reader and scholar.
Keywords: Van Riebeeck Society; Cape colony; Suez Canal; Dutch; English; Cape of Good Hope